2017
DOI: 10.5551/jat.39115
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Prognostic Value of Coronary Computed Tomography Angiography: High-Risk Plaque Characteristics in Asymptomatic Patients

Abstract: Aim: Coronary computed tomography angiography (CCTA) findings of positive remodeling (index > 1.1) and low-attenuation plaque (< 30 Hounsfield units) are recognized as CT-verified high-risk plaque (CT-HRP). Therefore, we investigated the incremental prognostic value of evaluation of plaque characteristics using CCTA in asymptomatic patients.Methods: Overall, 495 consecutive patients without any known coronary artery disease who underwent CCTA were included in this study. Patients who underwent revascularizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 43 publications
0
20
0
5
Order By: Relevance
“…Hoffman et al 34 ) reported that a significantly larger plaque area and positive remodeling were found in culprit lesions of patients with ACS, compared with patients with stable CAD. Positive remodeling has been recognized as a surrogate marker of plaque vulnerability 35 ) . In a landmark study, Motoyama et al 36 ) found that culprit lesions of patients with ACS more frequently had positive remodeling, low-attenuation plaque (< 30 HU), and spotty calcifications.…”
Section: Coronary Computed Tomography Angiographymentioning
confidence: 99%
“…Hoffman et al 34 ) reported that a significantly larger plaque area and positive remodeling were found in culprit lesions of patients with ACS, compared with patients with stable CAD. Positive remodeling has been recognized as a surrogate marker of plaque vulnerability 35 ) . In a landmark study, Motoyama et al 36 ) found that culprit lesions of patients with ACS more frequently had positive remodeling, low-attenuation plaque (< 30 HU), and spotty calcifications.…”
Section: Coronary Computed Tomography Angiographymentioning
confidence: 99%
“…Coronary computed tomographic angiography (CTA) provides valuable information not only about luminal stenosis but also about plaque characteristics. High-risk plaque (HRP: positive remodeling and/or low attenuation) determined by CTA was associated with a high risk of acute coronary syndrome (ACS) 8 10 ) . Modern CT equipment provides excellent images with less radiation exposure and lower contrast medium dose requirement, extending the potential use of CTA in preoperative assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Предполагается, что неоваскуляризация атеросклеротической бляш-ки является причиной «кольцевидного усиле-ния» [27]. Впоследствии исследователи подтвердили наличие «кольцевидного» усиления в АСБ симп-том-связанной коронарной артерии [28,29]. Manubu Kashiwagi et al сопоставили результаты КТ и ОКТ, в которых феномен «кольцевидного усиления» чаще наблюдался в АСБ (тонкокап-сульная фиброатерома) при КТ (специфичность 97%, чувствительность 44%), чем положитель-ное ремоделирование артерии и наличие участ-ка низкой рентгеновской плотности.…”
unclassified
“…Более того, это трудно охарактеризовать гистологически [25]. Послед-ние исследования МСКТ-АГ показывают, что «napkin-ring» демонстрирует различную частоту в зависимости от исследуемой популяции [29,33]. Тем не менее, в популяциях, где «napkin ring» распространен, признак был связан с не-стабильными АСБ [29,33].…”
unclassified
See 1 more Smart Citation